2012
DOI: 10.3402/tellusa.v64i0.11595
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sea ice cover changes on the Northern Hemisphere atmospheric winter circulation

Abstract: The response of the Arctic atmosphere to low and high sea ice concentration phases based on European Center for Medium-Range Weather Forecast (ECMWF) Re-Analysis Interim (ERA-Interim) atmospheric data and Hadley Centre's sea ice dataset (HadISST1) from 1989 until 2010 has been studied. Time slices of winter atmospheric circulation with high (1990–2000) and low (2001–2010) sea ice concentration in the preceding August/September have been analysed with respect to tropospheric interactions be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
227
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(246 citation statements)
references
References 33 publications
18
227
0
1
Order By: Relevance
“…The autumn Arctic sea-ice reductions during the several recent decades are generally located at the marginal ice zones with the most intensive reductions located at the Beaufort Sea and the East Siberia Sea (Screen et al 2013). Some previous studies reported a statistical relation between the winter negative NAO and the recent sea-ice reductions (Wu and Zhang 2010;Jaiser et al 2012). The pattern reported by those studies resembles the pattern associated with the autumn heat flux changes over the Pacific and Atlantic marginal regions presented in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The autumn Arctic sea-ice reductions during the several recent decades are generally located at the marginal ice zones with the most intensive reductions located at the Beaufort Sea and the East Siberia Sea (Screen et al 2013). Some previous studies reported a statistical relation between the winter negative NAO and the recent sea-ice reductions (Wu and Zhang 2010;Jaiser et al 2012). The pattern reported by those studies resembles the pattern associated with the autumn heat flux changes over the Pacific and Atlantic marginal regions presented in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The link between the NAO and sea ice cover has been investigated by several other studies Deser et al 2004;Kvamstø et al 2004;Seierstad and Bader 2009;Strong and Magnusdottir 2011;Jaiser et al 2012;Peings and Magnusdottir 2014). Despite varying conclusions, there seems to be widespread agreement that Arctic sea ice loss favors the negative mode of the NAO (Vihma 2014).…”
Section: Naomentioning
confidence: 99%
“…Another important atmospheric response attributed to amplified Arctic warming is a weakened polar vortex during middle to late winter (Cohen et al, 2014b;Kim et al, 2014). The weakened polar vortex is caused by increased poleward heat and equatorward momentum transport related to increased upward vertical wave activity flux (WAFz) and is associated with a stronger Siberian high (Cohen et al, 2007;Jaiser et al, 2012). The winter began with an anomalously strong polar vortex (Figure 5a, contours).…”
Section: Arctic Influence?mentioning
confidence: 99%